2021
DOI: 10.3389/fphys.2021.740121
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Heat Acclimation With Dehydration Does Not Affect Vascular and Cardiac Volumes or Systemic Hemodynamics During Endurance Exercise

Abstract: Permissive dehydration during exercise heat acclimation (HA) may enhance hematological and cardiovascular adaptations and thus acute responses to prolonged exercise. However, the independent role of permissive dehydration on vascular and cardiac volumes, ventricular-arterial (VA) coupling and systemic hemodynamics has not been systematically investigated. Seven males completed two 10-day exercise HA interventions with controlled heart rate (HR) where euhydration was maintained or permissive dehydration (-2.9 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…In contrast, no reduction in heart rate was observed post-acclimation during semi-recumbent exercise heat stress that was performed to obtain echocardiographic measures of cardiac function. There were also no changes in any of the markers of cardiac function measured during exercise Travers et al (2021). subsequently demonstrated that the addition of mild dehydration (∼3% body mass loss) during the heat acclimation protocol did not alter any of these results.Taken together, these studies provide limited evidence that heat acclimation elicits adaptations in cardiac function under normothermic rest and passive or active heat stress.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…In contrast, no reduction in heart rate was observed post-acclimation during semi-recumbent exercise heat stress that was performed to obtain echocardiographic measures of cardiac function. There were also no changes in any of the markers of cardiac function measured during exercise Travers et al (2021). subsequently demonstrated that the addition of mild dehydration (∼3% body mass loss) during the heat acclimation protocol did not alter any of these results.Taken together, these studies provide limited evidence that heat acclimation elicits adaptations in cardiac function under normothermic rest and passive or active heat stress.…”
mentioning
confidence: 76%
“…Travers et al. ( 2021 ) subsequently demonstrated that the addition of mild dehydration (∼3% body mass loss) during the heat acclimation protocol did not alter any of these results.…”
Section: Improved Thermoeffector Output and Lower Heart Rate Followin...mentioning
confidence: 94%
“…Increasing exercise intensity or elevations in T c and sympathoadrenal activity elevate heart rate during exercise [157,162,170,208], resulting in a shorter duration of diastolic filling and concomitant fall in end-diastolic volume [145,167,204,206,209]. These responses may be exacerbated further by dehydration and the associated concomitant hyperthermia and reduced circulating blood volume [44,197,200]. Experiments manipulating heart rate and blood volume during exercise in the heat with and without dehydration support the notion of a dual role in impairments in diastolic filling.…”
Section: Cardiac and Peripheral Mechanisms Regulating The Systemic Ci...mentioning
confidence: 88%
“…With incremental exercise in normothermic conditions, systolic twisting of the left ventricle increases [145] and end-systolic volume is maintained as exercise intensity increases from moderate to heavy/severe intensities despite elevated systolic pressure [145,148,149,192]. Afterload also appears to have minimal influence on the decline in Q with progressive exercise-induced dehydration in the heat, as arterial blood pressure is similar or slightly reduced compared to euhydrated responses [6,43,44,162,170,197,200].…”
Section: Cardiac and Peripheral Mechanisms Regulating The Systemic Ci...mentioning
confidence: 98%
See 1 more Smart Citation